The virtual duplicate in perspective (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This paper discusses the electronic trade notes in the context of Brazilian market, focusing on its historical evolution, since the beginning of the past century, when merchants started to take the customers signature on the duplicate of the bills, going through the evolution of doctrine and legal system, the mechanism of book entry credits, culminating with the recent judgments by Brazilian Superior Tribunal de Justiça, that have confirmed the possibility of judicial enforcement of electronic trade notes.
Keywords: negotiable instruments; electronic trade notes; book entry credits